Soy and Algae Combination Using Tempe Fermentation Method: A Proposed Opinion for the Development of Functional Food - ASSA, Youla Annatje; MAYULU, Nelly; SURYA, Reggie; TASLIM, Nurpudji Astuti; GUNAWAN, William Ben; SAMTIYA, Mrinal; KARTAWIDJAJA, Felicia; SETIAWAN, Aurielle Annalicia; WIJAYA, Alfredo; Nurkolis, Fahrul (Nutrición Clínica y Dietética Hospitalaria, 2023)
Backgrounds and Aims: Marine algae and plant-based protein have gained popularity among the most sought-after functional food ingredients and appeared as emerging trends for functional food. Combining ingredients that are well known to exert beneficial properties towards health can be considered an innovative strategy for developing novel functional foods. Each functional ingredient may contribute differently to health promotion and complement the beneficial properties of other components, thus increasing the overall health values of novel functional foods. In addition, these ingredients may exhibit synergistic activities that would improve the functionality of novel functional foods. Therefore, we propose that combining marine algae in the fermentation of tempe would be an innovative strategy to create a novel soybean-based functional food. This opinion-review article would provide a thorough insight into the conception, feasibility, and further research regarding the algae-tempe combination as a future functional food. Results and Conclusions: The supplementation of marine algae in the fermentation of tempe would open a new horizon about novel soybean-based functional food. Introducing marine algae in tempe production would bring additional compounds that might not be naturally present in soybeans. These compounds are subject to mold fermentation. We suggest that marine algae would improve the nutritional value of tempe by providing additional carbohydrates and protein. We suggest algal supplementation in tempe fermentation could be done by incorporating freeze-dried algal powder into the pre-boiled soybeans and starters before fermentation. We also suspect that algal polysaccharides might affect the texture of the tempe and bind water required for mold growth during fermentation. Therefore, the fermentation parameters for this product would need optimizing. Furthermore, the organoleptic analysis should also be the primary consideration and be conducted to measure consumer acceptance regarding the product since marine algae might bring specific flavors that might not be acceptable to some consumers.